2019
DOI: 10.3171/2017.12.jns172178
|View full text |Cite
|
Sign up to set email alerts
|

Risk of subsequent stroke, with or without extracranial-intracranial bypass surgery: a nationwide, retrospective, population-based study

Abstract: OBJECTIVE Although no benefits of extracranial-intracranial (EC-IC) bypass surgery in preventing secondary stroke have been identified previously, the outcomes of initial symptomatic ischemic stroke and stenosis and/or occlusion among the Asian population in patients with or without bypass intervention have yet to be discussed. The authors aimed to evaluate the subsequent risk of secondary vascular disease and cardiac events in patients with and without a history of this intervention. METHODS This retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Our previous studies compared the long-term postoperative neurofunctional outcomes of different revascularization strategies and suggested that direct bypass was more effective in preventing recurrent ischemic strokes than indirect bypass for ischemic MMD, although neurological function outcomes were similar [40][41][42]. However, the treatment options for hemorrhagic MMD remain controversial [17,43,44]. The mechanisms underlying hemorrhagic MMD have not been deeply understood and involve interactions between hemodynamic stress and thin arterial walls.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies compared the long-term postoperative neurofunctional outcomes of different revascularization strategies and suggested that direct bypass was more effective in preventing recurrent ischemic strokes than indirect bypass for ischemic MMD, although neurological function outcomes were similar [40][41][42]. However, the treatment options for hemorrhagic MMD remain controversial [17,43,44]. The mechanisms underlying hemorrhagic MMD have not been deeply understood and involve interactions between hemodynamic stress and thin arterial walls.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures of craniotomy or craniectomy were evaluated as severity of stroke. Stroke subtypes were classified into haemorrhagic stroke (ICD-9-CM codes 430–432; 430 subarachnoid haemorrhage, 431–432 intracerebral and other intracranial haemorrhage),16 17 ischaemic stroke (ICD-9-CM codes 433–436 excluding 433.x0) 18–20. Individuals with osteoporosis identified with a history of osteoporosis (ICD-9-CM code 733.0 or 733.1) or osteoporotic fractures, including vertebral fractures (ICD-9-CM code 805.2–805.9), humeral fracture (ICD-9-CM code 812), wrist fractures (ICD-9-CM code 813) and hip fractures (ICD-9-CM code 820)21 diagnosed before the index date, those with missing information and those aged younger than 50 years were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, EC-IC bypass surgery may be effective in stroke prevention [22,[27][28][29][30], but was hypothesized to benefit only hemodynamically compromised patients [17,21]. In addition, a high risk of hemorrhage stroke was observed in the early postoperative period, which may obscure the true benefit of revascularization of the ischemic brain [31].…”
Section: Introductionmentioning
confidence: 99%